アドホック・セルラ方式における端末の地域的に偏った移動と分布を考慮した通信トラヒック特性の解析 - 樺澤, 辰也; 中野, 敬介 (Transaction of the Japan Society for Simulation Technology, 2016)
An ad-hoc cellular system, which is a combination of a cellular system and direct communication, has been proposed to utilize limited frequency resources. In this system, a mobile terminal is directly connected to another terminal if these terminals are close to each other. Otherwise, the terminals communicate with each other via a base station of the cellular system. Performance analysis of the ad-hoc cellular system has been done in various situations. In this paper, we consider a mobility model where terminals go back and forth between a central point and their home points in the cell. This model assumes mobility of people between a shelter and their homes in a disaster situation. In this paper, we analyze teletraffic characteristics of an ad-hoc cellular system considering this mobility model. We analyze teletraffic characteristics of this system consisting of one cell assuming that terminals tend to gather a certain point with high probability by theoretical methods and computer simulation. Throughout analysis, we showed that direct communication works efficiently in this model, where terminals tend to gather a certain point. Furthermore, we showed how teletraffic characteristics are affected by the positon of the certain point and distribution of terminals.